Peningkatkan Hasil Belajar Praktik Computer Numerical Control (Cnc) Melalui Metode Resitasi Siswa Smk Negeri Teknologi Di Kota Makassar - Rusli Ismail (Seminar Nasional LP2M UNM, 2019)
This research is a classroom action research (Classroom Action research) which aims to improve learning outcomes Computer numerical control (CNC) Practice of State Vocational School Technology students in the city of Makassar. The object of this research is the students of class XI of Mechanical Engineering at SMK Negeri who participated in the practice of CNC totaling 24 students. The data collection technique used was through the provision of tests at the end of each cycle in accordance with the material taught previously in each cycle and direct observation of action implementation. This study identified an increase in student learning outcomes quantitatively, this increase was seen in the average score of student learning outcomes in class XI of Mechanical Engineering SMKN Technology in the city of Makassar, for each machining class. In SMKN 2 the initial test increased by 65 in the first cycle of 71.45 which then continued with the second cycle of 77.71. In SMKN 10 the initial test results obtained 65.38 increased in the first cycle to 71.75 and in the second cycle increased with 77.5 test results. In Vocational School 5 initial tests obtained 69.64 increased in cycle 2 of 75.18 then in the second cycle the results obtained increased 81.07 Qualitatively there was a change in the activeness and attention of students during the implementation of the action namely increasing student activity in carrying out tasks, fostering student courage in expressing opinions, as well as the creation of a favorable learning process condition for State Vocational School students in Makassar